Helping Mothers Escape Poverty: As European Policy Shows, Better Wages and Generous Social Supports are a Better Cure than Promoting Marriage - Karen Christopher (Luxembourg Income Study (LIS), 2002)
The belief that single motherhood is the pre-eminent cause of poverty in America has become a bipartisan cliché. The welfare reform enacted in 1996 was designed, among other things, to discourage single parenthood and to promote marriage. Yet a look at the experiences and policies of other nations suggests a more complex story of the causes and cure of poverty. Evidence from Europe shows that the remedy is increasing the economic resources available to low-income families-through better paying jobs that relieve poverty directly and social supports that reconcile paid employment with reliable parenting.
Keywords: 330; Alleinerziehende; Armutsbekämpfung; Sozialpolitik; EU-Staaten